Kanibalizm w literaturze odczytany przez pryzmat konkretnych części ciała - Radford, Kathryn (Er(r)go. Teoria - Literatura - Kultura, 2003)
Kathryn Radford Reading Literary Cannibalism through Specific Body Parts This article outlines how the modem cannibal myth functions on the basis of prior references in Western art and literature (mythemes). By tracing the importance of the heart and brain plus the eating thereof. the author points up a semantic shift from 'sacred heart' to 'secular brain'. The cannibal reappears at the body part which represents the ultimate; in other words, ultimate act and ultimate body part, the locus of many contemporary societal preoccupations (Kuru. CJT, transplants). The article refers specifically to the trilogy of Thomas Harris. in particular, Hannibal. This is an extract of a broader study of the real act of cannibalism in twentieth-century Western literature.